Advances in the Treatment of Colorectal Cancer with Peritoneal Metastases: A Focus on Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy - Youngbae Jeon; Eun Jung Park (The Ewha Medical Journal)
In stage IV colorectal cancer (CRC), peritoneal metastasis is associated with a poor prognosis. Hyperthermic intraperitoneal chemotherapy (HIPEC) after cytoreductive surgery (CRS) is an effective treatment option that offers survival benefits in patients with peritoneal metastatic CRC. For over the past several decades, a multitude of studies have been conducted on CRS and HIPEC for peritoneal metastatic diseases, and research in this area is ongoing. Proper patient selection and a meticulous preoperative assessment are crucial for achieving successful postoperative outcomes. The completeness of cytoreduction and the surgical techniques employed are key factors in improving oncologic outcomes following CRS and HIPEC. The role of HIPEC for both therapeutic and prophylactic purposes is currently being evaluated in recent clinical trials. This article reviews the fundamental principles of CRS combined with HIPEC and discusses recent clinical trials concerning the treatment of CRS and HIPEC in CRC patients with peritoneal carcinomatosis.